Risk factors for self-medication: an integrative review (Research, Society and Development, 2022)
The aim of this study was to investigate risk factors for self-medication. This is an integrative literature review, developed in the Scientific Electronic Library Online, PubMed and Latin American and Caribbean Literature on Health Sciences databases. For the controlled search, health descriptors were used, in English and Portuguese, with the combination of Boolean operators: “automedicação OR self-medication AND fatores de risco OR risk factors”. Inclusion criteria were articles published from July 2016 to July 2021, in Portuguese and English, nationally. Nineteen articles were selected for the final sample, developed in different Brazilian states. The risk factors for self-medication were classified as Behavioral, Environmental, Demographic, Physiological and Genetic. Among the most prevalent, the most advanced age group, the female gender, having chronic diseases and pain reports are mentioned. It is concluded that the risk factors for self-medication are related to the social, economic and cultural contexts of the Brazilian population. Investigating the risk factors for self-medication constitutes a strategy for the prevention of diseases, since it calls for new multiprofessional postures in favor of the cause.